Computational modeling of thermal therapy for porous osteosarcoma knee bone tumors using magnetized copper oxide nanoparticles - Muhammad Suleman; Usama Majeed; Sami Ullah Khan; Nermeen Abdullah; Nidhal Becheikh; Lioua Kolsi (Case Studies in Thermal Engineering)
Background: Osteosarcoma is malignant bone tumor in youth, affecting the distal femur the knee. The interaction of magnetized nanoparticles-induced hyperthermia identifies a minimal intrusive strategy for the tumor ablation, proposing alternatives to peak risk surgical resection. This thermal therapy may preserve the join functionality during the limb-salvage procedures. Objectives: This continuation presents a computational approach to simulating thermal treatment of porous knee Osteosarcoma tumors with applications of magnetized copper oxide nanoparticles. Porosity increases the nanoparticles penetration and thermal phenomenon, enhancing the treatment efficiency as well as tumor damage. The quantitative analysis is performed for all involved thermal therapy processes. Methods: A 3D tumor configuration mimicking the knee bone tissues has been generated with help of Bézier curves. A COMSOL Multiphysics has been used to model the diffusion and infusion of nanoparticles and heat generation. The nanoparticles movement is supported with convection-diffusion model, while Pennes’ bio-heat theory is followed to study the thermal impact in porous tissues. Results: Therapeutic temperatures (42–90 °C) has been resulted in 5–7 min of magnetic induction, enabling the effective tumor ablation without damaging any other tissues. Maximum nanoparticles concentration, temperature and tumor damage friction is examined at center of tumor. An accuracy of 85–90 % tumor damage has been resulted. Conclusions: The copper oxide nanoparticles assisted hyperthermia effectively targeted the porous osteosarcoma tumors, demonstrating potential for the minimally invasive treatment. The proposed model presents future applications in treating other cancers and designing smart bone scaffolds, justifying promising tool for optimizing thermal therapies in orthopedic interventions.